Interplay of silymarin and clove fruit extract effectively enhances cadmium stress tolerance in wheat (Triticum aestivum) - El-Sappah, Ahmed H.; Metwally, Mohamed A. S.; Rady, Mostafa M.; Ali, Hayssam M.; Wang, Linghui; Maitra, Pulak; Ihtisham, Muhammad; Yan, Kuan; Zhao, Xin; Li, Jia; Desoky, El-Sayed M. (Frontiers in Plant Science, 2023)
Osmoprotectant supplementation can be used as a useful approach to enhance plant stress tolerance. However, the effect of silymarin and clove fruit extract (CFE) on wheat plants grown under cadmium (Cd) stress has not been studied. Wheat seeds were planted in plastic pots filled with ions-free sand. A ½-strength Hoagland's nutrient solution was used for irrigation. Pots were treated with eight treatments thirteen days after sowing: 1) Control, 2) 0.5 mM silymarin foliar application [silymarin], 3) 2% CFE foliar application [CFE], 4) CFE enriched with silymarin (0.24 g silymarin L-1 of CFE) [CFE-silymarin], 5) Watering wheat seedlings with a nutritious solution of 2 mM Cd [Cd]. 6) Cadmium + silymarin, 7) Cadmium + CFE, and 8) Cadmium + CFE-silymarin. The experimental design was a completely randomized design with nine replicates. The Cd stress decreased grain yield, shoot dry weight, leaf area, carotenoids, chlorophylls, stomatal conductance, net photosynthetic rate, transpiration rate, membrane stability index, nitrogen, phosphorus, and potassium content by 66.9, 60.6, 56.7, 23.8, 33.5, 48.1, 41.2, 48.7, 42.5, 24.1, 39.9, and 24.1%, respectively. On the other hand, Cd has an Application of CFE, silymarin, or CEF-silymarin for wheat plants grown under Cd stress, significantly improved all investigated biochemical, morphological, and physiological variables and enhanced the antioxidant enzyme activities. Applying CFE and/or silymarin enhanced plant tolerance to Cd stress more efficiently. Our findings suggest using CFE-silymarin as a meaningful biostimulator for wheat plants to increase wheat plants' tolerance to Cd stress via enhancing various metabolic and physiological processes.